2017
DOI: 10.1021/acsmacrolett.7b00334
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of Recombinant Human Growth Hormone from Bioresorbable Poly(ester urea) Nanofibers

Abstract: Recombinant human growth hormone (rhGH) has been used clinically for several decades. However, rhGH has a short half-life in vivo and therefore for efficacy requires frequent subcutaneous injection, leading to pain and poor patient compliance. An effective rhGH delivery system able to continuously release rhGH over a comparatively long period (generally over a month) would be a significant clinical advance. In this study, a novel long-duration release strategy of rhGH was developed by encapsulating sugar glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Targeted nanocarrier delivery systems are primarily administered by bolus intermittent injections and infusions, with few options available for sustained delivery 7 . Sustained delivery platforms have proven highly advantageous for drug administration, particularly for long-term processes such as wound healing 8 , 9 , hormone therapy 10 , 11 , and transplant tolerance 12 , 13 , and incorporation of nanocarriers may further improve the efficacy and flexibility of these applications 14 , 15 . Due to the physicochemical similarities and cellular biodistributions between nanoscale materials and viruses, nanocarriers have demonstrated considerable advantages for the targeting and modulation of phagocytic antigen-presenting cells (APCs) that are critical for eliciting immune responses during vaccination and immunotherapy 1 , 2 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Targeted nanocarrier delivery systems are primarily administered by bolus intermittent injections and infusions, with few options available for sustained delivery 7 . Sustained delivery platforms have proven highly advantageous for drug administration, particularly for long-term processes such as wound healing 8 , 9 , hormone therapy 10 , 11 , and transplant tolerance 12 , 13 , and incorporation of nanocarriers may further improve the efficacy and flexibility of these applications 14 , 15 . Due to the physicochemical similarities and cellular biodistributions between nanoscale materials and viruses, nanocarriers have demonstrated considerable advantages for the targeting and modulation of phagocytic antigen-presenting cells (APCs) that are critical for eliciting immune responses during vaccination and immunotherapy 1 , 2 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…A sustained GH release system was created by stabilisation of the hormone within sugar glass nanoparticles, which were subsequently encapsulated in PCL or poly(ester urea) electrospun fibres. GH release was observed for a period of 6 weeks with minimal burst, and the released protein maintained its bioactivity in in vitro cellular assays [175].…”
Section: Other Examples 361 Hormone Deliverymentioning
confidence: 94%
“…Meng et al reported the synthesis of Pluronic F127 (PF127)/D-α-tocopheryl polyethylene glycol succinate (TPGS) micelle by thin-film hydration to specifically deliver proteins to the brain [23]. In another study, Gao et al reported the stabilization of recombinant human growth hormone (rhGH) by sugar glass NPs obtained from inverse micelles [24].…”
Section: Ii112 Polymer Self-assemblymentioning
confidence: 99%
“…As for the Bradford assay, the detection limits can vary from a kit to another but are usually ranging from 0.5 to 20 µg.mL -1 , with a possible modification when using microplates to perform the test. This technique has also been used for a wide variety of proteins: BSA [97,124], lysozyme [46,124], OVA, IgG [124], rhGH [24], human chitin binding domain-modified beta-lactamase (ChBD-BlaP)…”
Section: Iii113 Bicinchoninic Acid Assaymentioning
confidence: 99%
See 1 more Smart Citation